Clinical response and outcome in patients with multidrug resistant gram-negative infections - Masoume Malekolkottab; Lida Shojaei; Hossein Khalili; Mahsa Doomanlou (Wolters Kluwer Medknow Publications, 2017)
Objective: In this study, frequency and antimicrobial sensitivity pattern of multidrug resistant (MDR) microorganisms were evaluated in a referral teaching hospital in Iran. Methods: Patients with MDR Gram-negative pathogens were followed during the course of hospitalization. Demographic data, baseline diseases, type of biological sample, isolated microorganism, type of infection, antibiotic regimen before the availability of the culture result and change in the antibiotic regimen following receiving the antibiogram results, response to the treatment regimen, and duration of hospitalization and patient's outcome were considered variables for each recruited patient. Findings: In 71% of the patients, antibiotic regimens were changed according to the antibiogram results. A carbapenem alone or plus amikacin or ciprofloxacin were selected regimens for patients with extended-spectrum beta-lactamase (ESBL) infections. For patients with probable carbapenem-resistant Enterobacteriaceae infections, a carbapenem plus colistin was the most common antibiotic regimen. Clinical response was detected in 54.5% of the patients who were treated based on the antibiogram results. Clinical response was higher in the ESBL producers (ESBL-P) than the non-ESBL-P infections (75% vs. 52%). However, this difference was not significant (P = 0.09). Most nonresponders (80%) had sepsis due to Klebsiella species. Finally, 41.9% of the patients were discharged from the hospital and 58.2% died. Conclusion: Same as other countries, infections due MDR microorganisms is increasing in the recent years. This type of resistance caused poor clinical response and high rate mortality in the patients.